MHD Flow of a Viscous Fluid over an Exponentially Stretching Sheet in a Porous Medium. (30th April 2014) - Ahmad, Iftikhar; Sajid, Muhmmad; Awan, Wasim; Rafique, Muhammad; Aziz, Wajid; Ahmed, Manzoor; Abbasi, Aamar; Taj, Moeen
Abstract : Radiation effects on magnetohydrodynamic (MHD) boundary-layer flow and heat transfer characteristic through a porous medium due to an exponentially stretching sheet have been studied. Formulation of the problem is based upon the variable thermal conductivity. The heat transfer analysis is carried out for both prescribed surface temperature (PST) and prescribed heat flux (PHF) cases. The developed system of nonlinear coupled partial differential equations is transformed to nonlinear coupled ordinary differential equations by using similarity transformations. The series solutions for the transformed of the transformed flow and heat transfer problem were constructed by homotopy analysis method (HAM). The obtained results are analyzed under the influence of various physical parameters.